Desenvolvimento de um controlador para grupo motor gerador diesel de emergência através de CLP - VENEZA, Técio Barbosa (2019)
In this course conclusion work presents the development of a project to command an emergency diesel generator engine group to replace the existing command. It was necessary to do a retrofit to the drive motor-generator group due to control issues in default function components, already obsolete, need to increase the reliability and availability of the group. The project was developed with the use of a programmable logic controller as an alternative to the use of inspectors marketed by several companies in the sector in Brazil.